UPAYA BIDAN DALAM MEMBERIKAN PELAYANAN ANTENATAL CARE YANG BERKUALITAS PADA MASA PANDEMI COVID-19 DI PMB BIDAN DELIMA WILAYAH BANJARMASIN TIMUR - Yayuk Puji Lestari; Latifah Latifah (Jurnal Ilmu Kebidanan, 2023)
Background: The emergence of the COVID-19 virus outbreak has had an extraordinary impact on the world of health. The COVID-19 pandemic has made pregnant women worry about coming to the hospital and health center for check-ups for fear of contracting COVID-19, which has resulted in pregnant women coming to PMB. The increase in the number of visits during the pandemic has caused midwives because of their increased workload, reduced staff numbers due to self-regression, they are quarantined, infected, or have to care for friends and family. The method in this study is a qualitative research with a generic qualitative research approach. Results: This study shows that there were several strategies used by midwives when providing services during the COVID-19 pandemic, namely in the form of providing facilities and online consultations; Some of the midwives' obstacles when providing services are expensive facilities and infrastructure, there are insufficient patients who are infected with COVID-19; While providing services, midwives receive emotional, informational, informative and instrumental support. For the physical and psychological needs of midwives when providing services, namely a healthy diet, adequate rest, reducing stress and regular exercise. Conclusion: The most dominant strategy for midwives in providing services is filling the infrastructure; The obstacles that are often experienced are expensive facilities and infrastructure; when providing services midwives need all types of support; physical and psychological needs, namely a healthy diet, adequate rest, reducing stress and an exercise routine.